2011
DOI: 10.4321/s1575-06202011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Concordancia de las pruebas de tuberculina e Interferón gamma en población reclusa

Abstract: Objective: To study the agreement of Tuberculin Skin Tests (TST) and Interferon Gamma Release Assays (IGRA) when screening tuberculosis infection amongst inmates recently admitted to prison. Materials and Methods:Prospective study conducted in a prison during the months of May and June 2009. Inmates without a TB history, with previous TST negatives or without prior TSTs were included. Participants signed an informed consent form and the study was approved by an independent Ethical Committee. TST (positive 10 >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
2
5
2
5
Order By: Relevance
“…3 In our study, two risk factors were associated with the prevalence of positive TST: previous incarceration and length of detention; this is in line with previous studies. 20,21 In contrast to our results, prevalence of TST positivity reported in high-income countries is lower: 26.8% in Spain, 22 17.9% in Italy, 20 12-14% in Australia, 13 18% in the United States, 3 and 46.9% in Switzerland. 23 In low-middle-income countries, TST prevalence ranges between 48% in Pakistan, 24 52.4% in Nigeria, 25 60.8% in Brazil 26 and 88.8% in Malaysia.…”
Section: Discussioncontrasting
confidence: 96%
“…3 In our study, two risk factors were associated with the prevalence of positive TST: previous incarceration and length of detention; this is in line with previous studies. 20,21 In contrast to our results, prevalence of TST positivity reported in high-income countries is lower: 26.8% in Spain, 22 17.9% in Italy, 20 12-14% in Australia, 13 18% in the United States, 3 and 46.9% in Switzerland. 23 In low-middle-income countries, TST prevalence ranges between 48% in Pakistan, 24 52.4% in Nigeria, 25 60.8% in Brazil 26 and 88.8% in Malaysia.…”
Section: Discussioncontrasting
confidence: 96%
“…Interestingly, IGRA positivity was less likely among immunized people, in accordance with previous research suggesting the relevance of the IGRA screening test in LTBI evaluation [12,19]. The higher specificity of IGRA to detect M. tuberculosis infection [29] and the protective effect of BCG vaccination on M. tuberculosis infection [12] could explain our results.…”
Section: Discussionsupporting
confidence: 91%
“…However, according to a recent systematic review, the prevalence of LTBI among HCW by using IGRA in low-incidence countries was only 16% [27]. Also, the proportion of LTBI we found among TB contacts and inmates was higher than reported in other European settings [4, 14, 28, 29]. Our findings probably reflect the TB burden in Portugal, a country with one of the highest incidence rates (20.5 new cases and relapses of TB per 100,000 population) and with one of the lowest TB treatment success rates (37.3%) among European countries in 2018 [23].…”
Section: Discussionmentioning
confidence: 70%
“…Although much debate remains about the utility of TST in bacille Calmette-Guérin (BCG) vaccinated populations, the immunogenic effects of BCG wane after 8–10 years. 19 While numerous studies have shown that the majority of TST-positive, interferon-gamma release assay-negative discordances occur in BCG-vaccinated populations, 20,21 these are relatively infrequent. The WHO therefore supports the use of TST to detect LTBI in settings where BCG is used.…”
Section: Discussionmentioning
confidence: 99%